2004
DOI: 10.1111/j.1365-2850.2004.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ ethical perceptions about coercion

Abstract: In Finland, special attention has been paid to ethical questions related to the care of psychiatric patients and to the enhancement of patients' rights, yet the majority of the nurses participating in the survey did not perceive coercive measures as ethically problematic. More research on this issue as well as further education of the personnel and more extensive teaching of ethics in nursing schools are needed to support the ability of the psychiatric personnel to identify ethically problematic situations. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 31 publications
4
90
0
4
Order By: Relevance
“…Lind, Kaltiala-Heino (19) found that only a few nurses working in a psychiatric acute ward felt that coercion was ethically problematic. How does it happen that in one study the therapists felt guilt and shame, while in another only a few had problematic feelings?…”
Section: Vulnerability and Guilty Consciencementioning
confidence: 99%
“…Lind, Kaltiala-Heino (19) found that only a few nurses working in a psychiatric acute ward felt that coercion was ethically problematic. How does it happen that in one study the therapists felt guilt and shame, while in another only a few had problematic feelings?…”
Section: Vulnerability and Guilty Consciencementioning
confidence: 99%
“…D'Orio et al [5], for example, report a 39% reduction in coercion following introduction of a package which included enhanced access to expertise during emergency situations. Involvement in the use of these measures or witnessing their use can be highly distressing for both service users and staff [6][7][8] and few are likely to remain neutral about them. Attitudes toward different types of coercive measure are likely to vary between and within service user and staff groups but little is known about the preferences of staff and service users when comparing different measures.…”
Section: Introductionmentioning
confidence: 99%
“…Although inpatient nurses use coercive interventions, for some it does not present ethical problems [51] as they appear oblivious to practice issues and hold paternalistic attitudes. For some patients seclusion maybe a positive experience as it enables them to have a "quiet" time away from the busy ward environment and an opportunity for reflection.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of restrictions includes the risk of misuse of power and perceived punishment, even if the expressed purpose is good [6,26]. Nurses may experience negative feelings towards the distressed and/or disturbed patients who have been involved in the use of coercion [6,18,27] and feelings of discomfort can be produced [28]. In acute environments, staff may not have the necessary clinical skills or time to be able to manage distressed and/or disturbed patients, consequently resorting to other methods of containment.…”
Section: Open Accessmentioning
confidence: 99%